Atmosfera do ambiente de cafeterias: estudos de caso em Santa Maria/ RS - Benetti, Julia Pivetta (2023)
The coffee shop is a space of commercial service architecture and is also usually considered a place to take a break, a refuge from routine and not just an eating environment. Therefore, the atmosphere of these spaces must follow this form of use. This work aims to establish design guidelines for commercial gastronomic architecture applicable to coffee shop that assist in the design of these spaces. Firstly, parameters were established for choosing the studied coffee shops located in Santa Maria/RS. The research procedures developed include the application of an online questionnaire to help understand what users expect and think about a coffee shop. Exploratory visits were carried out in the coffee shops studied, in order to understand their characteristics and target audience. Assessments using physical-environmental inventory sheets, semi-structured interviews with the owners, technical managers and customers of the studied coffee shops and also systematic observations. The results of the online questionnaire served to understand how people see and use a coffee shop, what their preferences are, how they choose the coffee, what environmental characteristics they prefer and which contribute to people staying there. The exploratory visits made it possible to visualize the importance of having a target audience and thus attracting them to the coffee shop, whether through the menu offered, the technologies or the built space. It was also possible to visualize the diversity of the coffee shop business model, which can vary from small to large environments. Semi-structured interviews with the owners make it possible to understand the particularities and history of each coffee shop. Interviews with the architects provided an understanding of the design decisions made and the justification for the choice of materials and furniture. Interviews with customers made it possible to understand the reasons why customers frequent a determined coffee shop, what they like most and least about the environment. Systematic observations confirmed some answers from the online questionnaire and interviews with customers, helping to understand user behavior. Based on the results found, design guidelines were established for the coffee shop environment, which help professionals, architects or designers, to design these spaces.